Elaboración de un plan direccional de perforación utilizando las tendencias de la formación, para un pozo en el área de San Martín en el campo A (2018)
This project has the main objective of developing a directional drilling plan for a well in the A Field, located in the San Martin Area, taking into account the formation natural tendencies during the drilling process, with the purpose of optimizing drilling time and cost.